Efeitos de diferentes tempos de extração no teor e composição química do óleo essencial de folhas de pariparoba [Pothomorphe umbellata (L.) Miq.] - Mattana, Raquel de Souza [UNESP]; Almeida, Chrystian Iezid Maia e [UNESP]; Oliveira, Piero Felipe Camargo de [UNESP]; Lima, L. P. [UNESP]; Haber, Lenita Lima; Ming, Lin Chau [UNESP]; Marques, Marcia Ortiz Mayo [UNESP] (FapUNIFESP (SciELO), 2015)
The present work aimed to evaluate the influence of different times of extraction in the yield and chemical composition of the essential oil of “pariparoba” (Pothomorphe umbellate). Leaves of “pariparoba” were collected in the municipal district of Cajamar – state of São Paulo, Brazil, in June 2006. The adopted experimental design was completely randomized, with six times of extraction (90, 120, 150, 180, 210, and 240 minutes) and 4 repetitions. The extraction of the essential oil was accomplished by hydrodistillation, and the chemical analysis was performed in GC-MS. The time of extraction of 180 minutes provided greater yield of the essential oil (0.42%), and its chemical composition was not influenced by the different times of hydrodistillation. The main substances showed are D-germacrene (65.5%), alpha-selinene (9.7%), trans-caryophyllene (7.5%) and spathulenol (6.58%). The results of this work showed that the time of extraction affects the yield and the proportion of the chemical substances and it is recommended the extraction in up to 180 minutes.

O presente trabalho visou avaliar a influência de diferentes tempos de extração no teor e composição química do óleo essencial da espécie Pothomorphe umbellata. Folhas de pariparoba foram coletadas em Cajamar – SP, no mês de junho de 2006. O delineamento experimental adotado foi inteiramente casualizado, com seis tempos de extração (90, 120, 150, 180, 210 e 240 minutos) e 4 repetições. A extração do óleo essencial foi realizada por hidrodestilação e a análise química em CG-EM. O tempo de 180 minutos proporcionou maior rendimento do óleo essencial (0,42%), enquanto a composição química não foi influenciada pelos diferentes tempos de destilação. As principais substâncias identificadas foram: D-germacreno (65,5%), alfa-selineno (9,7%), trans-cariofileno (7,5%), e espatulenol (6,58%). Conclui-se que o tempo de extração afeta diretamente o rendimento e a proporção das substâncias químicas, recomendando-se a extração em até 180 minutos.
Effects of time of extraction in the yield and chemical composition of the essential oil of pariparoba leaves [Pothomorphe umbellata (L.) Miq.]
Keywords: Essential oil; Times of extraction; Hydrodistillation; Yield; Chemical composition; Pothomorphe umbellate; Óleo essencial; Tempos de extração; Hidrodestilação; Teor; Composição química; Pothomorphe umbellata